Fructooligosaccharides (FOSs): A Condensed Overview - Pedro Fernandes (Compounds, 2025)
FOSs are short-chain fructose-based oligosaccharides with notable functional and health benefits. Naturally present in various fruits and vegetables, FOSs are primarily produced enzymatically or microbially from sucrose or long-chain fructans, namely, inulin. Enzymes such as fructosyltransferase, β-fructofuranosidase, and endoinulinase are typically involved in its production. The chemical structure of FOSs consists of an assembly of fructose residues combined with a glucose unit. The increasing consumer demand for healthy foods has driven the widespread use of FOSs in the functional food industry. Thus, FOSs have been incorporated into dairy products, beverages, snacks, and pet foods. Beyond food and feed applications, FOSs serve as a low-calorie sweetener for and are used in dietary supplements and pharmaceuticals. As a prebiotic, they enhance gut health by promoting the growth of beneficial bacteria, aid digestion, improve mineral absorption, and help regulate cholesterol and triglyceride levels. Generally recognized as safe (GRAS) and approved by global regulatory agencies, FOSs are a valuable ingredient for both food and health applications. This review provides an updated perspective on the natural sources and occurrence of FOSs, their structures, and physicochemical and physiological features, with some focus on and a critical assessment of their potential health benefits. Moreover, FOS production methods are concisely addressed, and forthcoming developments involving FOSs are suggested.